Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Downes, Jamie K.; Rigby, Megan L.; Taylor, Richard S.; Maynard, Ben T.; MacCarthy, Eugene; O'Connor, Ian; Marcos-Lopez, Mar; Rodger, Hamish D.; Collins, Evelyn; Ruane, Neil M.; Cook, Mathew T. (Frontiers in Marine Science, 2017)
Amoebic gill disease (AGD) caused by Neoparamoeba perurans, has emerged in Europe as a significant problem for the Atlantic salmon farming industry. Gross gill score is the most widely used and practical method for determining AGD severity on farms and informing management decisions on disease mitigation strategies. As molecular diagnosis of AGD remains a high priority for much of the international salmon farming industry, there is a need to evaluate the suitability of currently available molecular assays in conjunction with the most appropriate non-destructive sampling methodology. The aims of this study were to assess a non-destructive sampling methodology (gill swabs) and to compare a range of currently available real-time PCR assays for the detection of N. perurans. Furthermore a comparison of the non-destructive molecular diagnostics with traditional screening methods of gill scoring and histopathology was also undertaken. The study found that all molecular protocols assessed performed well in cases of clinical AGD with high gill scores. A TaqMan based assay (protocol 1) was the optimal assay based on a range of parameters including % positive samples from a field trial performed on fish with gill scores ranging from 0 to 5. A higher proportion of gill swab samples tested positive by all protocols than gill filament biopsies and there was a strong correlation between gill swabs tested by protocol 1 and gross gill score and histology scores. Screening for N. perurans using protocol 1 in conjunction with non-destructive gill swab samples was shown to give the best results.